Updating customs services list as one of the means of transformation - I. Yu. Sofiyannikova (Вестник университета)
The article studies existing state customs services list, means of their provision, and problems associated with their implementation and realization.   The purpose of the study is to analyze customs services sphere transformation considering increasing digital maturity of economy.   The relevance of the study is due to the need to expand service provision in the state customs services sphere considering orientation to the interests of the end user (foreign economic activity participant, business representative, individuals, and legal entities).   The main objectives are to identify problematic aspects of the customs authorities service sphere and to propose and justify the need to introduce new non-regulated state customs services.   The article used both theoretical research methods such as the analysis of current legislation, as well as the works of modern researchers in this field and empirical methods such as practical substantiation of options for improving state control effectiveness and mechanism for providing state customs services. On the basis of the analysis of the customs services currently provided, the most demanded and unclaimed ones have been identified. The study result is the proposal of possible options for implementing non-regulated state customs services to expand the customs author-ities service sphere.